Modern Requirements for Future Professionals in The Field of Journalism (Eurasian Journal of Media and Communications, 2022)
There are currently no manuals or books on identifying new technologies in journalism in Uzbekistan, although they are in short supply. The purpose of writing the article is to analyse the requirements for young people who are conducting research in this field and are just entering the field of journalism, using new methods.